In vitro replication of infectious bursal disease virus in established lymphoid cell lines and chicken B lymphocytes. - Hirai, K (1979)
The in vitro susceptibility of chicken lymphocytes to a wild strains of infectious bursal disease virus was investigated by using immunofluorescence and virus assays as infection criteria. A variety of Marek's disease lymphoblastoid cell lines, all of thymus (T-cell) origin, were refractory to virus exposure. However, a bursa (B-cell)-derived lymphoblastoid cell line from an avian leukosis virus-induced tumor was highly susceptible. Viral antigen appeared in the cytoplasm of 20 to 30% of the cells, and large amounts of cell-free virus were released, with maximum yields occurring by 3 days postinfeciton. The virus also replicated in a small percentage of normal lymphocytes prepared from lymphoid tissues and peripheral blood of chickens. Pretreatment of the lymphocytes, with heat-inactivated anti-B-cell serum or with antiserum against fowl immunoglobulin M before inoculating them with the virus blocked the virus infection; no blocking occurred with anti-T-cell serum or with specific antiserum against fowl immunoglobulin G or immunoglobulin A. This suggests that surface immunoglobulin M-bearing B-lymphocytes were the target cells for infection.